Perancangan dan Pembangunan Aplikasi Mobile Manajemen Stok Material Proyek untuk CV Lingga - Ariel Sudarsono; Raphael Lee; Novan Wijaya (MDP Student Conference, 2026)
Amidst rapid digital development, the need for an efficient material management system has become increasingly important. This study aims to design and develop a mobile application for managing project material stock at CV Lingga. The previously used paper-based manual recording system caused various issues, including data inaccuracies, delays in information delivery, and difficulties in monitoring stock in real time. The development method applied in this study is the Waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The developed application provides project management features, recording of incoming and outgoing materials, and weekly report generation. The implementation of the system is proven to improve data accuracy, accelerate administrative processes, and facilitate centralized, real-time material stock monitoring.